CHARACTERISTIC, ORIGINAL AND FORMING CONDITION OF GRAINED SEDIMENTS IN SURFICIAL SEDIMENTS OF TONKIN GULF - Thanh, Dinh Xuan; Nghi, Tran; Lan, Nguyen Thanh; Tha, Hoang Van (Vietnam Journal of Marine Science and Technology, 2008)
Based on  original characteristics,  the  grained size  surficial sediments  on bottom  Tonkin  Gulf was  divided into  3 groups: provenance  of sediments  related to  igenous and sedimentwy rocks, provenance of sediments are materials of late  Pleistocene weathering crust  and provenance  of bioturbance  materials. Especially,  the  second group  was  detailed classified by  mineral and chemical compositions,  such as:  lateritzed curdles,  clastics  rich in iron, clastics rich in Ca;  and iron, cancite clatics.Sediments what originated from igenous and sedimentaJy rock are distributed around Bach Long Vi Island at 50 - 60 water depth. They were supplied from Bach Long Vi Island or continental. The continental provenance of sediment was transported by ancient river systems what formed in the regression phase in late Pleistocene (Q13b). Destroyed weathering crustal sediments are originated from uppermost of late  Pleistocene marine sediments (m Q13b) what affected by marine wave dynamic in Flandrian transgression phase.